The Effect of Professionalism on Employee Performance with Organizational Commitment as an Intervening Variable - Vendy Tri Purwantoro; Endang Suswati; Umi Muawanah (SAFE-Network, 2026)
The purpose of this study is to examine and analyze the influence of professionalism on organizational commitment, the influence of professionalism on employee performance, the influence of organizational commitment on employee performance, and the influence of professionalism on employee performance through organizational commitment. This study employs an explanatory research method. The sample consists of 47 employees of the Malang City Civil Service and Human Resources Agency. The sampling technique used was a census. The statistical analysis used was SmartPLS. The study's findings confirm that professionalism not only has a significant direct impact on boosting employee commitment and performance, but also has indirect effects. A competent work attitude and strong work ethic have been shown to strengthen employee loyalty to the organization, which in turn leads to increased productivity and collective performance.